Length of hospital stay and associated treatment costs for patients with susceptible and antibiotic-resistant Salmonella infections: a systematic review and meta-analysis - Isabel Frost; Kaja Abbas; Nichola R Naylor; Yeonhee Kim; Omar Mukhtar Salman; Chaelin Kim; Mateusz Hasso-Agopsowicz; Heidi Au; Yubin Lee; Anna Bzymek; Kamila Majgier; Ana Laura Moldoveanu; et al. (BMJ Open)
Objectives The global disease burden of Salmonella infections in 2017 included 135 900 deaths caused by Salmonella Typhi and Paratyphi and 77 500 deaths caused by invasive non-typhoidal Salmonella, with increasing antimicrobial resistance (AMR) exacerbating morbidity, mortality and costs. The aim of our systematic review and meta-analysis is to estimate the length of hospital stay and associated treatment costs for patients with susceptible and antibiotic-resistant Salmonella Typhi, Paratyphi and non-typhoidal Salmonella infections.Design Systematic review and meta-analysis.Data sources We searched EMBASE, Medline/PubMed, Scopus, Hinari and LILACS databases for studies published between 1 January 2005 and 15 May 2024, with no language restrictions.Eligibility criteria We included 30 studies that reported the length of hospital stay or treatment costs for patients with susceptible or antibiotic-resistant Salmonella Typhi, Paratyphi and non-typhoidal Salmonella infections. We excluded studies with sample sizes of less than 30 patients, those focused on non-human subjects and those not reporting our outcomes of interest.Data extraction and synthesis Two reviewers independently screened studies and extracted data on the length of hospital stay and associated costs, with monetary values converted to 2019 USD. We aggregated data according to GDP per capita quantiles using a random-effects meta-analysis. We conducted a quality assessment using an adapted Joanna Briggs Institute tool.Results Patients with drug-resistant Salmonella infections had longer hospital stays, with an additional 0.5–2.2 days compared with drug-susceptible Salmonella infections. Based on our meta-analysis, the mean hospital stay for typhoidal Salmonella infections was 6.4 days (95% CI 4.9 to 7.8) for drug-susceptible cases and 8.4 days (95% CI 5.1 to 11.7) for resistant cases in the lowest income quartiles. While there were insufficient data to perform a pooled analysis, individual studies inferred that treatment costs for resistant typhoidal Salmonella infections were higher than for susceptible infections, and resistant non-typhoidal Salmonella infections had longer hospital stays and higher costs compared with susceptible infections. Data were scarce from high-Salmonella-burden countries, particularly in sub-Saharan Africa and parts of Asia.Conclusions Patients with antibiotic-resistant Salmonella infections experience a greater healthcare burden in terms of hospitalisation length and direct costs compared with those with susceptible infections. We highlight the economic burden of AMR in Salmonella infections and emphasise the need for preventive measures.